Parallel simulation for solving intertwined spiral problem using NEUCOMP2 - Sulaiman, Md. Nasir; Evans, D. J. (Penerbit Universiti Kebangsaan Malaysia, 1997)
NEUCOMP2 is a parallel Neural Network Compiler for a shared-memory parallel machine. It compiles a program written as a list of mathematical specifications of Neural Network (NN) models and then translates it into a chosen target program which contains parallel codes. In this paper we present the performance results for intertwined spiral problem on popular NN models. The models are the Backpropagation, Kohonen, and Counter propagation models. NEUCOMP2 was developed on the Sequent 8000 computer system at PARC.